Large boron‐interstitial cluster modelling in BF3 plasma implanted silicon. Issue 1 (9th December 2013) - Essa, Z.; Cristiano, F.; Spiegel, Y.; Qiu, Y.; Boulenc, P.; Quillec, M.; Taleb, N.; Zographos, N.; Bedel‐Pereira, E.; Mortet, V.; Burenkov, A.; Hackenberg, M.; et al.
Abstract BF3 plasma immersion ion implantation (PIII) is a promising technique in the race for highly boron doped P+/N ultra‐shallow junctions (USJs) in complementary metal oxide semiconductor (CMOS) silicon technologies. Implantation conditions used in BF3 PIII lead to high super‐saturations (≥1 × 1020 cm–3) of both boron and silicon interstitial atoms in the implantation region. In such conditions, very large loop‐shaped boroninterstitial clusters (BICs) are formed during subsequent thermal anneals, as confirmed by transmission electron microscopy (TEM) measurements. In this study, amorphizing BF3 PIII implants (10 keV, 5 × 1015 cm–2) followed by different thermal anneals were carried out in order to investigate the large BICs precipitation. A "large BICs" model based on moments approach allowed to reproduce the experimental data including boron diffusion profiles (obtained by SIMS) and boron electrical activation obtained by Hall effect sheet resistance measurements. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)